Kajian dan Rumusan Projek Infrastruktur Jaringan pada Industri Hospitality - Akbar Juliansyah; Dyah Susilowati; Muhammad Yunus (Puslitbang Sekawan Institute Nusa Tenggara, 2019)
The Hospitality industry is increasingly improving its services to be able to grow as a tourism sector grows. The indication of the growth of the industry can be seen from the rise of international chains that enter or participate in developing their business in Indonesia. In principle, the Chain Hotel is a group of Hotels that is a hotel chain with services that are equal after star hotel equivalence. For that hotel owners who will join a chain of hotels that have been formulated by the chain hotels and usually refer to standards that apply globally / globally. The terms of information technology, chain hotels have implemented standards that follow World standards. This is a technology that is leading to the information system. This is a concern of every hospital industry player to implement. Thus this research is expected to provide infrastructure standards for hotels, especially according to the appropriate ANSI / TIA / EIA standards. The Research Methodology used a continuous development improvement cycle where the cycle is formed into 4 stages, namely Research Formulation and Requirements Analysis, Problem Design and Solutions, Analysis and Discussion of Formulation of Solutions and Suggestions in Framework of Continuous Improvement. The results of this study formulate a template and the contents of a network infrastructure project document in the form of a structured caling system (SCS) and ANSITIA /EIA